Effects of Liming to Near-neutral pH on Vitis vinifera L. - Wooldridge, J.; Louw, P.J.E.; Conradie, W.J. (South African Journal of Enology and Viticulture, 2016)
Wine grape vines are sensitive to soil pH and liming. The effects of pre-plant liming at rates sufficient to promote average soil pH levels (1M KCl) of 5.05 (unlimed, treatment L0), 5.64 (L1) and 6.56 (L2) in two wine grape (scion) varieties and four rootstocks five years after planting were investigated over six seasons in a factorial field trial at Stellenbosch. Yields tended to decrease in the sequence: L0 > L1 > L2, and were significantly (P = 0.05) lower in L2 than in L0. Conversely, cane masses increased progressively with lime application rate, with L1 exceeding L0 by 11.0% and L2 exceeding L1 by 13.0%. These increases were significant. Compared to L0, liming decreased the ratio of yield to cane mass by 13.6% in L1 and 28.8% in L2, but increased Ca:Mg ratios in the soil and petioles. Wine quality was significantly better from L0 than L2. Petiole N concentrations were above normal in all treatments. Suppressed yields and wine quality in the limed treatments were attributed to a lime-induced imbalance between vegetative and reproductive growth, possibly exacerbated by increased Ca:Mg ratios and excess nitrogen.